Active behaviour change safety interventions in the construction industry: A systematic review - Mullan, Barbara; Smith, L.; Sainsbury, Kirby; Allom, Vanessa; Paterson, H.; Lopez, A. (Elsevier, 2015)
© 2015 Elsevier Ltd. The aims of this paper were to systematically review the evidence for the effectiveness of active behaviour change safety interventions in the construction industry; and to determine the intervention characteristics most commonly associated with effectiveness in reducing injury rates and improving safety behaviour - intensity/frequency/duration, behaviour change techniques (BCTs) and theory-base. An electronic literature search (June 2014) was conducted to identify eligible interventions: those involving active involvement from workers/management in the construction industry; targeted one/both of the primary outcomes. All intervention designs involving construction workers aged >18 years, published in English and in a peer-reviewed journal were included. Fifteen studies were included, half of which successfully improved injury rates. Longer interventions and those that included active/volitional BCTs (feedback/monitoring rather than instruction/information) were more effective. The methodological quality of the interventions was poor and use of theory was inconsistent and infrequent. Despite some positive results, very few interventions achieved all their aims. More rigorous, theory-driven research is needed to structure intervention efforts and determine the mechanism of action of effective interventions.